Library of future - Zahimi, Ahmad Ariez Hazariel; Omar, Luqman; Ahmad, Amal Harrith; M. Said, Salasiah (Universiti Teknologi MARA, Kedah, 2018)
First of all, our library will serve a lots of materials about what will happen in future and what rarely happen in this world. Then, we will serve a high quality services with high tech devices and system. In our opinion, people typically get interested to something that rarely happen like the phenomenal things and things that will happen in the future including prediction. Therefore, this will be a great project and something new to us. Last but not least, this library project will increase the knowledge of our library users and will give a lot of advantages to people. Our library more futuristic than others library and lots high quality services also the first library that serve the material about future.